THE THEORY OF BILLINGUALISM IN THE ASPECT OF NEUROLINGUISTICS - Ergashova, Munavvar Dilsiroj qizi (INTERNATIONAL CONFERENCES, 2022)
This article deals with the basic theory of bilingualism in the aspect of neurolinguistics.